Same-Sex Families (in Slovenia): The New Minority? - Sobočan, Ana Marija (Calitatea Vieții, 2013)
The paper focuses on same-sex families, which are becoming a more visible family reality also in societies which don’t legally recognize same-sex partnerships and don’t allow adoption for same-sex partners. It discusses the realities of same-sex families in Slovenia, their life-world, their practices in the struggle for social recognition, as well as for their own secure position in two worlds: one of family and one of homosexuality. The discussion is based on the research about same-sex families in Slovenia: sixteen parents from same-sex families were interviewed in nine interviews, which were each conducted twice in the period between 2008 and 2011. The findings are valuable in shedding light on the shifts between visibility and minority position, which can also be used in forming suggestions for supporting these families. Also importantly, the paper familiarizes the readers with the life-world of same-sex families, still quite absent from the public discourse.